Barriers and facilitators for access and utilization of reproductive and sexual health services among Female Sex Workers in urban and rural Maharashtra, India - Shewale, Suhas; Sahay, Seema (Frontiers in Public Health, 2022)
Background The public health interventions among Female Sex Workers (FSWs) have mainly addressed HIV/ STI prevention. The focus of the HIV prevention program on FSWs' Reproductive and Sexual Health (RSH) has been limited, thus, rendering them at a higher risk of unintended pregnancies, delayed pregnancy detection, and utilizing unsafe abortion methods. Methods A multistakeholder analysis was performed to study access and use of RSH services among FSWs in urban and rural India. Between January 2016 and June 2019, a qualitative grounded theory approach was used to explore the FSWs' perspectives and experiences about services pertaining to HIV prevention, Antenatal Care (ANC), child delivery, abortion, and pregnancy prevention. Using purposive and convenience sampling, 29 In-Depth Interviews (IDIs), 2 Focus Group Discussions (FGDs) and 22 Key Informant Interviews (KIIs) were conducted with consenting FSWs and indirect stakeholders, respectively. Verbatim translated data was entered in NVivo12 Software and analyzed inductively. Results The following themes emerged: (1) Condomless sex, unintended pregnancy, vertical transmission, (2) Signs/ indication used for pregnancy detection causing delay (3) Pregnancy prevention methods used, (4) Pregnancy prevention or AIDS prevention, (5) Legal formalities as a barrier to access RSH, (6) Differential facility preference. Conclusion Pregnancy prevention is a greater motivation for condom use than HIV prevention among FSWs. Therefore, there is an emerging need to reallocate public health resources and redesign policies to meet the RSH needs of FSWs, especially for the prevention of unintended pregnancies. FSW-focused Information Education Communication (IEC) strategies for RSH service utilization are essential to reduce the burden of unintended pregnancies. The National HIV Targeted Intervention (TI) program needs to include pregnancy testing services and information to non-barrier contraceptive methods. An ambient policy environment calls for examining the need for male involvement in pregnancy, family planning and abortion decisions.